Factors influencing HIV knowledge among Indian men: A cross-sectional study - Jenica Barnwal; Dilwar Hussain (PLoS ONE, 2025)
Human Immunodeficiency Virus (HIV) is one of the critical global health issues, posing severe risks due to its ability to weaken the immune system progressively. Without a cure or effective vaccine, HIV remains a serious health threat in developing countries, especially in South Asia, sub-Saharan Africa, and countries such as India. This study explores the socio-economic and demographic determinants of comprehensive knowledge of HIV among Indian men aged 15–54 years. The study used descriptive statistics and binary logistic regression models to examine the predictors of comprehensive knowledge of HIV among men using the latest round of the National Family Health Survey data, 2019−21 (NFHS-5). Results indicate that comprehensive knowledge of HIV was more prevalent among non-adolescents and was positively associated with being unmarried, educated, wealthier, and residing in urban areas. Logistic regression models revealed that men with higher education were nearly three times more likely to have comprehensive knowledge of HIV than those without formal education. Furthermore, men with full mass media exposure, residing in the Western and North-Eastern regions of India, working in the service sector, and belonging to the richest wealth quintile were significantly more likely to possess comprehensive knowledge of HIV. These findings highlight the importance of targeted interventions focusing on education, economic empowerment, and media outreach to address disparities in HIV awareness among men across different socio-economic and demographic backgrounds in India.